BENTUK PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM PENERBITAN KARTU KREDIT DAN MASALAH YANG TIMBUL - Fenny Eria (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTIrregularities in the use of credit cards that can be distinguished based on their behavior, namely: Irregularities committed by the holder of the credit card. The efforts irregularities committed by the bank to address a variety of irregularities committed by the credit card holder or employers, such as: To overcome the use of credit cards that exceed the credit limit with a transaction conducted under the floor limit, the issuer (bank) for the first time will give a warning to credit card holders not to use credit cards that exceed the credit limit, even though the cardholders have sufficient funds. If the violation of the credit limit is still being done despite warnings were given three times, then the issuer (the bank) can cancel the card and put it into the black list and credit card holders are obliged to pay off all the outstanding obligations; To cope with the credit card holders often late in paying bills account, the issuer (the bank) will alert the cardholder credit. With provide penalties for late paying accounts; Actions or steps taken by the bank to cope with the entrepreneur's action of granting a higher price on the credit card holder is: Bank for the first time will give a warning to employers to refrain from actions that violate them.If the transaction is still breaking acts committed by employers, then the issuer (the bank) will further sanction. Recent efforts made by the issuer (the bank) is the cancellation / termination of the agreement. Actions or steps taken by the bank to address the actions the employer conducts doubling sales draft or fictitious transaction are: Bank will give a warning to businessmen and accompanied by sanctions that will refuse payment if the bill transaction fictitious transactions that have not been paid by the issuer. If the bill is fictitious transactions had already been settled by the issuer and the bills are included in the credit card holder's name and his credit card number used in the fictitious transactions, the issuer (the bank) will cut / charge back bill that has been paid by the issuer.Form of legal protection for employers in the event of delays are outside sales draft mistakes entrepreneurs. Legal protection for employers in connection with the above, the employer can state that the issuer in default for not paying a bill on legal transactions, in which employers, in the transaction have done his duty properly. Under these circumstances, the employer is entitled to claim compensation for losses resulting from liquefaction rejection sales draft. This is in accordance with the provisions of Article 1239 of the Civil Code. Keywords: Legal Protection, Credit Card Issuance, the problems posed.